ä»¥é©¬å†…åˆ©ä¸ä¸“äºŒæ ¡äºŒå¹´çº§å¦ç”Ÿçš„æ±‰å—å¦ä¹ æ¦‚å†µç ”ç©¶ - Saputra, Norman; ., Ina; ., Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
æ‘˜è¦ï¼šå¦ä¹ æ±‰å—æ˜¯å¦ä¹ æ±‰è¯è¿‡ç¨‹ä¸çš„å›°éš¾ä¹‹ä¸€ã€‚æ‰€ä»¥æœ‰æ•ˆåœ°æé«˜æ±‰å—æ•™å¦çš„è´¨é‡æ˜¯æ±‰è¯æ•™å¦ä¸éžå¸¸é‡è¦çš„ä»»åŠ¡ã€‚ä¸ºäº†äº†è§£åœ¨å°å°¼çš„å¦ç”Ÿå¯¹æ±‰å—æŽŒæ¡æƒ…å†µï¼Œç¬”è€…åœ¨ä»¥é©¬å†…åˆ©ä¸ä¸“äºŒæ ¡è¿›è¡Œç ”ç©¶ã€‚ç¬”è€…å‘è¯¥æ ¡çš„å¦ç”Ÿåˆ†å‘è°ƒæŸ¥é—®å·ï¼Œæœ‰å…³å¦ç”Ÿå¯¹æ±‰å—å¦ä¹ å…´è¶£å’Œæ±‰å—çŸ¥è¯†äº†è§£æƒ…å†µã€‚å¦å¤–ï¼Œä¹Ÿå‘å¦ç”Ÿè¿›è¡Œæµ‹è¯•ï¼Œä»Žè€ŒèŽ·å¾—å¦ç”Ÿå¦ä¹ æ±‰å—çš„å…·ä½“éš¾ç‚¹ã€‚é€šè¿‡åˆ†æžä¸Žç»Ÿè®¡è°ƒæŸ¥ä¸Žæµ‹è¯•ç»“æžœä¹‹åŽï¼Œç¬”è€…å‘çŽ°ä»¥é©¬å†…åˆ©ä¸ä¸“äºŒæ ¡äºŒå¹´çº§å¦ç”Ÿç›®å‰å¯¹æ±‰å—çš„æŽŒæ¡ä¸æ˜¯å¾ˆç†æƒ³ï¼Œç‰¹åˆ«æ˜¯å¯¹æ±‰å—ç»“æž„ï¼ˆç¬”ç”»ã€ç¬”é¡ºã€åæ—ï¼‰ä¸å¤ªäº†è§£ï¼Œå¹¶ä¸”ä»–ä»¬ä¹Ÿä¸å¤ªä¼šè®¤è¯»æ±‰å—ã€‚ç¬”è€…å¸Œæœ›æœ¬è®ºæ–‡èƒ½å¤Ÿæå‡ºè§£å†³å¦ç”Ÿå¦ä¹ æ±‰å—éš¾ç‚¹çš„å»ºè®®ï¼Œä»¥åŠæé«˜æ•™å¸ˆæ•™æ±‰å—çš„æ•ˆçŽ‡ã€‚ Â å…³é”®è¯ï¼šæ±‰å—ï¼Œæ±‰å—æ•™å¦ï¼Œæ±‰å—å¦ä¹ æƒ…å†µ Abstract:LearningChinese charactersis one of thedifficulties inthe process oflearning Mandarin. Sothe mostimportant taskin teaching Mandarinis effectively improve the quality in teachingChinese characters. In order to understandIndonesianstudentin learning Chinese characters situation, Author doing research for student in ImmanuelII vocational highschool.Firstly,Author distributed questionnaires for students,the questionnaires are about studentâ€™s interest and Mandarinknowledge in learning Chinese characters situation. In addition,Author also doing test for Student to obtainthe specificdifficulties oflearningChinese characters.After analyzing, countsurvey and the test results, Author foundatImmanuelIIvocationalhigh schoolsecond year students do not understand Chinese characters well, especially in the structureof Chinese characters(strokes andradicals), and readingChinese characters.Hope thispapercan solvethe problemsinlearningChinese characters, as well as toimproveteacherâ€™s efficiency in teaching Chinese characters. Â Key Words: Chinese Characters, Teaching Chinese Characters, Situation in LearningChinese Characters